Soft‐tissue landmarks for tibial baseplate rotational alignment in total knee arthroplasty: A cadaveric study. Issue 8 (21st June 2022) - Eseonu, Onyedikachi; Mactier, Mhairi; Ferguson, Eilidh; Quondamatteo, Fabio; Blyth, Mark; Jones, Bryn
Abstract: The tip of the tibial tubercle (TTT) is used to assess tibial baseplate rotation in total knee arthroplasty (TKA); however, it can be difficult to palpate and visualize intraoperatively. Several more easily accessible soft‐tissue structures have been proposed as intraoperative assessments, including the patellar tendon's medial border (MBPT) and the junction of the medial third of the patellar tendon (mt‐PT). No studies have described the relationship between the TTT and these proposed landmarks. The aims of the study were to (1) determine the relationship of the soft‐tissue landmarks to the TTT and (2) identify any sex differences in these measures. Measurements of the position of these soft‐tissue landmarks relative to the TTT were made on 56 cadaveric knees (28 female) by two observers at the level of the standard tibial cut (10 mm distal to the lateral tibial plateau). The results obtained were compared by sex and side. On average, 50.7% (SD 6.79, range 33.1%–63.1%) of the patellar tendon footprint was medial to the TTT. There were no significant differences between the sexes or left and right lower limbs. However, there was large variability in the position of all the soft‐tissue landmarks relative to the TTT. The results indicate that, on average, the patellar tendon footprint is evenly spread around the TTT. However, there is a large variability in the anatomical relationship between the soft‐tissue landmarks and the TTT. Caution is advised if relying on these structures intraoperatively.